Mucopolysaccharidosis type VII associated with hydrops fetalis: histopathological and ultrastructural features with genetic implications. Issue 3 (March 1997) - Molyneux, A J; Blair, E; Coleman, N; Daish, P
Abstract : A case of mucopolysaccharidosis type VII (MPS VII, beta glucuronidase deficiency) causing fatal hydrops fetalis in the third trimester is presented. The diagnosis was suspected on histopathological examination by the presence of foam cells in many of the viscera and foamy change in the placental Hofbauer cells. Electron microscopy showed empty cytoplasmic inclusion bodies within macrophages and in the Hofbauer cells. Enzyme assay of cultured fibroblasts showed markedly deficient beta glucuronidase activity, thus confirming the diagnosis. A detailed and thorough histopathological examination of hydrops fetalis cases is important to detect subtle features of inherited metabolic disorders. Use of a structured necropsy protocol is recommended for cases of non-immune hydrops. Electron microscopy is a useful adjunct to light microscopy in cases where an inherited metabolic disorder is suspected. Precise necropsy diagnosis is important as there are implications for genetic counselling and possible prenatal diagnosis in subsequent pregnancies.